Preserving Keroncong Orchestra Group: A Study Of OK. Waseso In Bumijawa Tegal (Jurnal Seni Musik, 2021)
The regeneration of players, singers, and keroncong orchestra groups is happening in various regions in Indonesia until now. This condition indicates the process of inheritance of keroncong music between generations continue. This also happened in Bumijawa, Tegal Regency, which has the O.K Waseso. The problem discussed in this paper is how to preserve keroncong music carried out by O.K Waseso in Bumijawa, Tegal Regency. The research was conducted with qualitative methods. Data was collected using observation, interviews, and documentation. The data validity techniques were carried out by triangulation, and interactive model analysis. The results showed that the conservation efforts carried out by O.K Waseso for keroncong music were depicted through three activities, namely the protection, development, and utilization of keroncong music.